Recommendations for implementation of cluster policy in modern Russia - T. V. Fadeeva (Омский научный вестник: Серия "Общество. История. Современность")
The aim of the study is to study the experience of implementing cluster policy in the Russian Federation and offer recommendations for improving cluster policy and strengthening cluster processes. The article presents the results of the analysis of clusters and cluster policy in Russia. During the research, general scientific and special methods are used: analysis and synthesis, comparison and generalization, system analysis. As a result of the study, the driving forces of the functioning of clusters, the risks of implementing cluster policy in Russia and a list of limiting factors when choosing clusters-objects for financing are identified. The article reveals the peculiarities of cluster policy in Russia and gives recommendations for conducting cluster policy based on the domestic experience of clustering. In contrast to the existing ones, the recommendations proposed in the article are novel, since they take into account the current stage of development at which cluster associations in Russia are located. When developing the recommendations, the latest trends in the organizational development of clusters in an innovative economy are taken into account. The presented developments will be useful to public authorities in the formation of regional programs for the development of clusters in the regional economy, as well as for making decisions on the support of clusters